Pest control and treatment of stored grains for use in animal feed (Research, Society and Development, 2020)
The grains used in feed are susceptible to chemical and physical changes, which cause changes in their nutritional values, can harm animal health and performance, as well as favor the appearance of toxic substances, such as mycotoxins. Thus, the sanitary quality of the grains is important, which in turn is related to the production and storage conditions (temperature and humidity). In storage, grain quality must be maintained for long periods, and the adoption of practices to combat insects and prevent fungi and bacteria is a necessary strategy. The objective was to describe the main methods used in pest control and treatment of stored grains for use in animal feed. The methodology adopted was bibliographic research, with information obtained from documentary sources. Among the alternatives to minimize losses in grain storage, there are integrated pest management and good grain and / or product storage practices. In situations of infestation of grains stored by pests, chemical, physical and biological methods are tools for pest control and grain treatment. The choice of method will be based on the availability of the alternative, the complexity of applying the technique, the economy, the production of quality feed, as well as the lowest environmental impact.